P022 Severe disease activity in UC is associated with mucosal hypoxia measured endoscopically. (16th January 2018) - Rowan, C R; Brown, E; Ryan, E; Taylor, C; Doherty, G A
Abstract: Background: Tissue hypoxia has been shown to be a key microenvironmental regulator of mucosal barrier function and inflammation in pre-clinical models of colitis. However, the role of mucosal hypoxia in the pathogenesis of UC has yet to be extensively studied in IBD patients. Visible light spectroscopy can be utilised to measure the haemoglobin (Hb) oxygen saturations (%) colonic mucosa during endoscopy. Carbonic anhydrase 9 (CA-9) is a hypoxia-inducible protein and endogenous marker of hypoxia. The aim of this study was to compare mucosal oxygen saturations in normal and inflamed colonic mucosa in UC patients and assess relationship with disease activity. Methods: Patients undergoing colonoscopy were prospectively recruited in a single academic centre, with >3800 IBD patients. Endoscopies were performed using CO2 insufflation. Measurements of colonic mucosal Hb saturations were performed segmentally and from zones of transition from inflamed to normal mucosa, using an endoscopic probe (applied to intact mucosa) and tissue oximeter (T-Stat System, Spectros).Endoscopic severity was graded using the endoscopic Mayo score. Mucosal biopsies were obtained to grade histologic activity and for protein analysis. Results: 38 patients were included in this study; n = 7 controls, n = 31 UC; male=25 (65.7%). The median age of UC patients was 39 years (IQR 34.6- 55.9). n = 5 had Mayo 0, n = 9 Mayo 1, n = 11 Mayo 2 and n = 6 Mayo 3 activity. At the time of the procedure, five patients were on biologic therapy, five immunomodulators and six on steroids. The median rectal saturation in the control group was 76.2% (IQR 73–80), compared with 77% (IQR 73.8–80.6) in the UC cohort (Mayo 0–3 inclusive) ( p = 1.00). There was no significant difference across any colonic segment between these two cohorts. The median rectal mucosal O2 saturation in Mayo 0 was 77.6% (77.4–81.2), Mayo 1: 80.6% (77–83.8), Mayo 2: 75.4% (73.5–79.2) and Mayo 3:73.3% (68.7–74.8) ( p = 0.02). CA9 protein expression was significantly higher in biopsies with Mayo 2–3 activity compared with Mayo 0-1 disease. Conclusions: Mucosal O2 saturation is significantly decreased in severely active UC and oxygen signalling pathways are activated suggesting that mucosal hypoxia is an important determinant of disease severity in UC. These observations suggest the potential for oxygen signalling pathways as novel therapeutic targets.